Cognitive developments in economics - Rizzello, Salvatore, 1963- (Routledge frontiers of political economy ;, 2003)
This book proposes an interdisciplinary approach to the study of human problem solving, choice, decision-making and change, to explain economic transactions, and the nature and evolution of organisations and institutions.